El Niño impacts in the Inkomati-Usuthu catchment - Montes, Carlo (International Food Policy Research Institute, 2023)
Near normal but increasing temperature anomalies are predicted for the Inkomati-Usuthu catchment from August 2023 to January 2024. Predicted near-normal rainfall anomalies turn negative as summer 2023/34 approaches in the catchment. A reduction in rainfall, higher than normal temperatures and evaporative demand, along with drought conditions induced by the 2023 El Niño event can be expected for the Inkomati-Usuthu catchment from January to March 2024 and likely until the next wet season.